212k views
4 votes
In ΔSTU, \text{m}\angle S = (2x+10)^{\circ}m∠S=(2x+10) ∘ , \text{m}\angle T = (3x-9)^{\circ}m∠T=(3x−9) ∘ , and \text{m}\angle U = (6x-19)^{\circ}m∠U=(6x−19) ∘ . Find \text{m}\angle T.M∠T.

User Roundrobin
by
5.2k points

1 Answer

2 votes

Answer:
\text{m}\angle T=45^(\circ)

Explanation:

Given: In ΔSTU,
\text{m}\angle S = (2x+10)^(\circ) ,
\text{m}\angle T = (3x-9)^(\circ),
\text{m}\angle U = (6x-19)^(\circ)

To find:
\text{m}\angle T.

We know that the sum of all the angles of a triangle is
180^(\circ).

In ΔSTU,


\text{m}\angle S+\text{m}\angle T+\text{m}\angle U=180^(\circ)\\\\ 2x+10+3x-9+6x-19=180\\\\ 11x-18=180\\\\11x =180+18\\\\11x=198\\\\x=(198)/(11)\\\\ x=18


\text{m}\angle T = (3(18)-9)^(\circ)\\\\=(54-9)^(\circ)\\\\= 45^(\circ)

Hence,
\text{m}\angle T=45^(\circ)

User Tim Trueman
by
4.6k points